Applied Microscopy - Kim, Ki Woo.; Kim, Do Hyang; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer.)
Applied Microscopy is a peer-reviewed journal sponsored by the Korean Society of Microscopy. The journal covers all the interdisciplinary fields of technological developments in new microscopy methods and instrumentation and their applications to biological or materials science for determination of structure and chemistry. All articles published by Applied Microscopy follows Continuous Article Publishing (CAP), so there will be no delay in publication upon acceptance and articles will be published on an irregular basis. .
Keywords: Materials science; Materials Science